Aus dem Nichts ins Nichts: Zu Fatih Akins Aus dem Nichts und Feridun Zaimoglus German Amok (Rosso, Marta und Sbarra, Stefania: Literatur der (Post-)Migration Komplexitäts- und Identitätsfragen der deutschsprachigen Literatur im globalisierten Zeitalter, 2023)
As a critical reflection to the discourse surrounding the ‘Berlin Republic’ and the demand for a redefinition of the German national identity, the last two decades have seen the emergence of various works by artists labeled as ‘migration background’ that deal with German historical and memory culture. Fatih Akin’s political thriller Aus dem Nichts and Feridun Zaimoglu’s novel German Amok examine migration from a genuinely postmigrant perspective. This broadening of the perspectival focus generates a different understanding of history and society, which through its disillusioning and irritating effect allows a critical examination of social power relations and deficits in norms and values.